Pulmonary haemodynamics of the yak, cattle, and cross breeds at high altitude. Issue 9 (September 1986) - Anand, I S; Harris, E; Ferrari, R; Pearce, P; Harris, P
Abstract : The pulmonary arterial pressure of Ladakhi yaks, at an altitude of about 4500m, was not significantly different from that found in yaks bred at low altitude. The pulmonary arterial resistance, however, was slightly but significantly increased in the high altitude group. It is concluded that the yak has adapted genetically to high altitude by largely eliminating the hypoxic pulmonary vasoconstrictor response. The pulmonary arterial pressure and resistance were significantly higher in indigenous Himalayan cattle than in the yaks. The dzo (cow X yak) had pulmonary haemodynamics similar to those of the yak. Half of the stols (dzo X bull) had pulmonary haemodynamics similar to those of the yak, while in the other half the findings resembled those in the cow. The results suggest that the genetic attenuation of the hypoxic vasoconstrictor response is transmitted as a simple autosomal dominant.